(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
Non-standard aluminium-silicon alloys of the eutectic type are complexly modified. The alloys were subjected to T6 heat treatment at different artificial aging parameters. The influence of the working parameters of the dispersion hardening process on the microhardness of the α-solid solution and the macrohardness of the alloys was investigated. The influence of alloying elements on the phase composition of the alloys is discussed.